Ventilatory acclimatisation is beneficial for high-intensity exercise at altitude in elite cyclists. Issue 8 (16th November 2016) - Townsend, Nathan E.; Gore, Christopher J.; Ebert, Tammie R.; Martin, David T.; Hahn, Allan G.; Chow, Chin-Moi
Abstract: Aim: The aim of this study was to examine the relationship between ventilatory adaptation and performance during altitude training at 2700 m. Methods : Seven elite cyclists (age: 21.2 ± 1.1 yr, body mass: 69.9 ± 5.6 kg, height 176.3 ± 4.9 cm) participated in this study. A hypoxic ventilatory response (HVR) test and a submaximal exercise test were performed at sea level prior to the training camp and again after 15 d at altitude (ALT15). Ventilation ( V E ), end-tidal carbon-dioxide partial pressure (PET CO2 ) and oxyhaemoglobin saturation via pulse oximetry (SpO2 ) were measured at rest and during submaximal cycling at 250 W. A hill climb (HC) performance test was conducted at sea level and after 14 d at altitude (ALT14) using a road of similar length (5.5–6 km) and gradient (4.8–5.3%). Power output was measured using SRM cranks. Average HC power at ALT14 was normalised to sea level power (HC%). Multiple regression was used to identify significant predictors of performance at altitude. Results : At ALT15, there was a significant increase in resting V E (10.3 ± 1.9 vs. 12.2 ± 2.4 L·min −1 ) and HVR (0.34 ± 0.24 vs. 0.71 ± 0.49 L·min −1 ·% −1 ), while PET CO2 (38.4 ± 2.3 vs. 32.1 ± 3.3 mmHg) and SpO2 (97.9 ± 0.7 vs. 94.0 ± 1.7%) were reduced ( P  < .05). Multiple regression revealed ΔHVR and exercise V E at altitude as significant predictors of HC% (adjusted r 2  = 0.913; P  = 0.003). Conclusions : Ventilatory acclimatisation occurred during a 2 wk altitude training camp in elite cyclists and a higher HVR was associated with better performance at altitude, relative to sea level. These results suggest that ventilatory acclimatisation is beneficial for cycling performance at altitude.